Green technologies in the knowledge space: Insertion and the moderating role of industry knowledge bases - Françoso, Mariane Santos [UNESP]; de Lima Avanci, Vanessa; Mazoni, Alysson Fernandes (Springer Nature, 2024)
This paper discussed how green technological domains are inserted into the Brazilian knowledge space. We investigated whether the insertion of technologies into the Brazilian knowledge space is affected by the fact that these technologies are green or non-green, the potential moderating effect of the industry knowledge bases with which technologies are associated, and the differences regarding the insertion of green and non-green technology domains across industries. We considered Brazilian patent and industry data from 1997 to 2020 and a multilevel analysis to answer these questions. Our results indicated that green technological domains are intensely combined with other domains, but their structural embeddedness is still low. The characteristics of sectoral knowledge bases influenced the insertion of green technologies into the national knowledge space since these technologies are more deeply embedded in the knowledge space when associated with less mature knowledge bases.
Keywords: Green technologies; Knowledge base; Knowledge space; Networks; O30; Q55; Technological change